Co‐expression changes of lncRNAs and mRNAs in the cervical sympathetic ganglia in diabetic cardiac autonomic neuropathic rats. Issue 8 (19th December 2016) - Li, Guilin; Sheng, Xuan; Xu, Yurong; Jiang, Huaide; Zheng, Chaoran; Guo, Jingjing; Sun, Shanshan; Yi, Zhihua; Qin, Shulan; Liu, Shuangmei; Gao, Yun; Zhang, Chunping; et al.
Abstract: Cardiac autonomic neuropathy in Type 2 diabetes (T2D) is often a devastating complication. Long non‐coding RNAs (lncRNAs) have important effects on both normal development and disease pathogenesis. In this study, we explored the expression profiles of some lncRNAs involved in inflammation which may be co‐expressed with messenger RNA (mRNA) in superior cervical and stellate ganglia after type 2 diabetic injuries. Total RNA isolated from 10 pairs of superior cervical and stellate ganglia in diabetic and normal male rats was hybridized to lncRNA arrays for detections. Pathway analysis indicated that the most significant gene ontology (GO) processes that were upregulated in diabetes were associated with immune response, cell migration, defense response, taxis, and chemotaxis. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway revealed that most of the target genes of the lncRNAs were located in cytokine–cytokine receptor interactions, the chemokine signaling pathway and cell adhesion molecules, which were involved in T2D. Gene co‐expression network construction showed that the co‐expression network in the experimental rats consisted of 268 regulation edges among 105 lncRNAs and 11 mRNAs. Our studies demonstrated the co‐expression profile of lncRNAs and mRNAs in diabetic cardiac autonomic ganglia, suggesting possible roles for multiple lncRNAs as potential targets for the development of therapeutic strategies or biomarkers for diabetic cardiac autonomic neuropathy. © 2016 Wiley Periodicals, Inc. Abstract : Diabetic autonomic neuropathy was confirmed by HRV. GO processes and KEGG pathway results from lncRNA microarray revealed that most of the target genes of the lncRNAs were located in cell adhesion molecules, chemokine signaling pathway, et al. The coding‐non‐coding gene co‐expression network showed that lncRNAs and mRNAs were closely related.